EFL Teachers' Belief, Knowledge and Practices in Using Dictionaries - Elih Sutisna Yanto (University of Muhammadiyah Prof. DR. HAMKA, 2016)
This paper reports the survey results of 20 EFL teachers regarding their beliefs, knowledge and practices in using dictionaries in their classes at English education programme of a state university in Karawang - West Java, Indonesia. The questionnaire consists of four parts. The first part investigates the profile of the participants as dictionary users. The second part reports the results of teachers’ knowledge with regard to dictionary use through the lexicographic survey. The third part presents the results of EFL teachers’ general preconception about dictionaries. The fourth part presents teachers’ belief in the value of dictionaries for students. Finally, this paper suggests teachers how to utilize dictionaries in the classroom activities. Though the teacher participants are somewhat small, certain tendencies emerge as they show familiarity with dictionaries as an indivisible part of English language learning kit; they also agree that students need to be taught how to use dictionaries.